Pengabdian Masyarakat Berbasis Moderasi Beragama: Upaya Pencegahan Perundungan di SMP Negeri 1 Wonotunggal - Rita Istik Maliyah; Arsan Shanie; Zaina Maulani Fauziyah Latif; Imam Hafid Al-Ghazali; Ali Topan (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
The socialization program "Stop Bullying: Stop the Hate and Let's Spread the Love" is part of the Real Work Lecture (KKN) activities carried out at SMP Negeri 1 Wonotunggal, Wonotunggal Village, Wonotunggal District, Batang Regency. This program aims to increase students' awareness of the dangers of bullying and promote a harmonious friendship environment without violence. Through lecture methods, discussions and interactive activities such as positive affirmation and express yourself sessions, students are encouraged to understand the impact of bullying and how to prevent it. The implementation of the values of religious moderation in this program emphasizes the importance of respecting differences, rejecting violence, and building solidarity among students. The results of this program show active participation from students and support from the school in efforts to prevent bullying, with the hope of creating a safe and comfortable school environment for all students.